Intra-Urban Air Temperature Distribution, Urban Heat Island and Thermal Comfort Implications in A Subtropical City - E. Krüger; E. Dumke; F. Mendonça (International Journal of Architectural Engineering Technology, 2015)
Unlike most of the Brazilian hot-humid cities, subtropical Curitiba experiences thermal discomfort due to cold during most of the year, with the coldest air temperature occurring in winter. Due to rapid urbanization, the Metropolitan Area has been faced with critical environmental problems. Urban microclimate patterns exhibit considerable variability; particular areas of the city alternate between cool islands and heat islands, resulting in different outdoor thermal comfort levels. The objective of this work is twofold: 1) to characterize intra-urban air temperature differences and their impact on outdoor thermal comfort in Curitiba; 2) to assess the yearlong Urban Heat Island (UHI) effect and its effect on indoor thermal comfort levels. For that, a series of independent measurements and field monitoring campaigns, both outdoors and indoors, were analyzed. Results point to a great variability in intra-urban temperature differences and derived outdoor comfort levels. With regard to predicted UHI effects in low-cost dwellings, indoor comfort due to heat was found to prevail over the year; the ’net effect’ between heat stress in summer and cold stress in winter point towards a prevalence of heat stress indoors.